2020
DOI: 10.1109/tit.2019.2945776
|View full text |Cite
|
Sign up to set email alerts
|

A New Bound on Quantum Wielandt Inequality

Abstract: A new bound on quantum version of Wielandt inequality for positive (not necessarily completely positive) maps has been established. Also bounds for entanglement breaking and PPT channels are put forward which are better bound than the previous bounds known. We prove that a primitive positive map E acting on M d that satisfies the Schwarz inequality becomes strictly positive after at most 2(d − 1) 2 iterations. This is to say, that after 2(d − 1) 2 iterations, such a map sends every positive semidefinite matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In [39] it is shown that p(T ) ≤ (D 2 − d + 1)D 2 . This result has been recently improved [36] to p(T ) ≤ 2(D − 1) 2 . The order O(D 2 ) is optimal just by invoking the optimality of the classical Wielandt inequality.…”
Section: A Natural Question Arisesmentioning
confidence: 89%
“…In [39] it is shown that p(T ) ≤ (D 2 − d + 1)D 2 . This result has been recently improved [36] to p(T ) ≤ 2(D − 1) 2 . The order O(D 2 ) is optimal just by invoking the optimality of the classical Wielandt inequality.…”
Section: A Natural Question Arisesmentioning
confidence: 89%
“…Motivated by this, the concept of a primitive quantum channel was introduced in [15] as follows (see also [14] for more recent work). Definition 4.4.…”
Section: Joint Primitivity For Entanglement Breaking Channels and Sto...mentioning
confidence: 99%
“…In this paper, we contribute to this study with an investigation of an important class of quantum operations, which are given mathematically by completely positive trace-preserving maps on matrices, called entanglement breaking channels [4,7]. We bring two key notions from matrix theory to their study by identifying stochastic matrix representations for the channels, and, built on this, we conduct an analysis of the primitivity [14,15] of such channels based on corresponding matrix primitivity [6,11]. More specifically, we show how every so-called Holevo form of an entanglement breaking channel induces a certain stochastic matrix representation that has the same non-zero spectrum as the channel.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we confirm that the exponent conjectured in [PGVWC07] is indeed equal to two. After finishing the articles the authors learned that a related topic has been recently studied by Rahaman in [Rah18]. Under additional positivity assumptions the author proves an O(D 2 ) bound for the index of primitivity.…”
Section: Introductionmentioning
confidence: 99%